Prevalence of Smoking and its related behaviors and beliefs among secondary school students in Riyadh, Saudi Arabia - Al Nohair, Sultan Fahad (International Journal of Health Sciences, 2011)
Objective: To estimate the prevalence of smoking among secondary school students in National Guard area of Riyadh, and explore the reasons for the smoking and the attitude of non-smoker toward smoking habit. Design: A cross-sectional study was conducted in June 2009. By random sampling technique 255 students were enrolled from secondary school of National Guard area, Riyadh, Saudi Arabia.Â A self-administered questionnaire was used for data collection. Results: Current smokers represented 28.6% of the students. The most common reasons for smoking were: having free time (81.6%), for the relief of stress (63.2%) and seeing some of their teachers smoking (61.8%). Most of the smokers started the habit before the age of 15 years old (89%). 84% of non-smokers suggested to ban smoking in public places. 42.2% of students were planning to start smoking in future. Religion was the most important reason for not smoking among non smokers. Conclusion: The prevalence of smoking is big enough a problem to be considered as a warning for an impending epidemic Health education provision should have a greater role in schools Governmental commitment and social support are vital if health education and awareness and especially quit smoking programs are to be implemented and sustained. Key Words: Secondary school student, smoking, shisha, magha, Riyadh.